KESANTUNAN BERBAHASA SURAT-SURAT NABI MUHAMMAD KEPADA PARA RAJA - Ubaidillah, Ubaidillah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
This research was intended to look at the speech acts and politeness forms used by Prophet Muhammad. Moreover, it was also aimed to know the secret use of politeness on various speech acts in the lettersto the kings. The letters analyzed in this discussion were the letters containing a call to embrace Islam to the three kings of great kingdoms outside the Arabian Peninsula, Abyssinia al-Najasy (Ethiopia), Emperor Heraclius (Roman), and Kisra (Persia). The language analysis methodof Eunar Haugen was used in this research. Searle (1969) speech acts and Leech (1983)politeness was used as thetheory. The result showed that the letters mostly used a form of indirect speech acts with imperatives. In any form of speech used contained politeness maxims formulated by Leech used without recourse. The use of different linguistic politeness makes different influence on the king recipients. Once it is united to convince the recipients, it will make them sure to accept Islam.DOI: 10.15408/a.v3i2.3622